The Effect of Information Asimmetry On Earnings Management In Companies That Conduct An Initial Public Offering (IPO) On The Indonesia Stock Exchange (IDX) - Riski Hernando (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2018)
This study aims: to determine the effect of information asymmetry on Earnings Management in companies that carry out initial public offering on the Indonesia Stock Exchange in the period before go public, when go public, or after go public.Design and methodology: Sampling in this study is to use the purposive sampling method, where the company to be studied must certain criteria. The number of companies used as research samples based on predetermined criteria is 142 companies. The population in this study are banking/financial companies, service companies, and trading companies that made initial public offering on the Indonesia Stock Exchange (IDX). Analysis techniques are carried out with simple linear regression analysis techniques. The analytical method uses descriptive statistics, data quality tests, and hypothesis testing. Test the quality of the data in the form of classic assumption test which includes: normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Hypothesis testing uses the t test to test the coefficient partially with a significant level of 5%.Results: The test results prove that information asymmetry has a significant effect on earnings management during and after conducting an IPO, but when go public does not pass the heteroscedasticity test. The test results also prove that information asymmetry has no significant effect on earnings management before the IPO. Regression results indicate that the coefficient of determination possessed by the variables observed before, during, and after the IPO are respectively R-square= 0.039, 0.121, and 0.221. This means that the influence of the independent variables on the dependent variable is 3.9%, 12.1% and 22.1%.Originality/value: the addition of research variables to the independent variables can be done considering there are about 96.1%, 87.9%, and 77.9% influenced by other variables not included in this research model.Keywords: Asimmetry Information, Earnings Management, Initial Public Offering (IPO).